Cannabis Regulation: A Comparative Study in Indonesia, Turkey, and Morocco - Yayi Intan Pratiwi; Murat Kubilay Cengiz; Aymen Mouhin (Kosmik Hukum, 2023)
The purpose of this comparative study is to analyze the differences in legal and policy approaches between the three countries in dealing with the issue of cannabis use and distribution. This research uses a comparative descriptive approach by collecting data from various sources such as legal regulations, government reports, and related literature. The results of the analysis show that Indonesia, Turkey, and Morocco have different approaches to regulating Cannabis. Indonesia adopts a very strict approach by imposing heavy penalties for cannabis-related offenses. On the other hand, Turkey allows the medical use of cannabis under certain conditions and has reduced legal sanctions against offenses of using small amounts of cannabis. This was also done by Morocco in 2021. In Morocco, it has relaxed some aspects of cannabis regulation and directed efforts more towards rehabilitation than punishment. The comparative study in this article provides a deeper understanding of the variations in legal and policy approaches to the regulation of cannabis drugs in Indonesia, Turkey, and Morocco. The implications of these different approaches may provide valuable insights for other countries facing similar challenges in regulating cannabis. Keywords: Medical Cannabis, Comparative Law, Legality of Cannabis